Deteksi Dini Kolesterol, Asam Urat, Dan Glukosa Darah Pada Orang Tua Siswa RA Avicenna Sebagai Upaya Pencegahan Penyakit Tidak Menular - Andirwana; Fenti A Tupanwael; Untari; Evi Hudriyah Hukom; Fatimah (STIKES Columbia Asia Medan, 2025)
Non-communicable diseases (NCDs) such as hypercholesterolemia, hyperuricemia, and hyperglycemia are common health problems among adults and can develop into cardiovascular diseases and diabetes if not detected early. This community service activity was carried out to provide education on risk factors, prevention, and control of cholesterol, uric acid, and blood glucose levels among parents of students at RA Avicenna in Sorong City, as well as to conduct examinations of these three parameters as an early detection effort. The methods used included interactive counseling using presentation media, question-and-answer discussions, and health checks using point-of-care testing (POCT) devices. A total of 23 respondents participated, ranging in age from 22 to 55 years. The results showed that 22 individuals had normal blood glucose levels and 1 individual had high glucose levels. Nine people had normal cholesterol levels, eight were in the borderline category, and six had high cholesterol levels. Five participants had normal uric acid levels, while 18 had elevated uric acid levels, for which additional education and recommendations for further medical examination were provided. In conclusion, educational activities combined with health screening proved effective in increasing community awareness and motivation to prevent NCDs early.